Red cell alloimmunisation following intrauterine transfusion and the feasibility of providing extended phenotype‐matched red cell units. Issue 5 (17th September 2014) - Doyle, B.; Quigley, J.; Lambert, M.; Crumlish, J.; Walsh, C.; Adshead, S.; Woolfson, M.; McParland, P.; Culliton, M.; Fitzgerald, J.
SUMMARY Objectives To analyse the incidence of additional alloantibody formation following intrauterine red cell transfusion and to evaluate the feasibility of providing extended phenotype‐matched red cells in future intrauterine transfusion (IUT). Background IUT is performed in severe, life‐threatening fetal anaemia, usually in alloimmunised pregnancies. Its complications include the formation of additional alloantibodies to other red cell antigens. Materials and methods This was an 11‐year retrospective, observational study of additional alloantibody formation in patients receiving IUT in the National Maternity Hospital, Dublin. The study included evaluation of the donor population in the Republic of Ireland (RoI) with regards to the feasibility of providing extended phenotype‐matched units in future IUT. Results Following IUT, 22% of mothers formed additional red cell alloantibodies. In 67% of cases, the transfused donor red cells expressed the cognate antigen. Suitable donors are available for most combinations of Fy, Jk and Ss antigens. Conclusions In our population, it is feasible to provide more extensively phenotype‐matched red cells for future IUT. These can be supplied from the current donor pool with no significant extra phenotyping required. We consider their provision to be a reasonable proactive step in a known at‐risk group.